2008
DOI: 10.1016/j.ypmed.2008.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Walking and inflammatory markers in individuals screened for type 2 diabetes

Abstract: word Count = 164Main text word count = 2184 Number of Tables = 1 Number Method: Physical activity, adipocytokine, high-sensitivity C-reactive protein and fasting insulin measurements were available for 400 individuals screened for type 2 diabetes. Of the 400 participants, 56% were diagnosed with normal glucose control, 36% with prediabetes and 8% with diabetes.Results: Multivariate statistical analysis showed that those who reported walking for at least 30 minutes on at least five days per week had lower lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
1
16
0
1
Order By: Relevance
“…In an animal model, sedentary rats eating a high‐fat diet had greater body weight, more body fat, and gingival oxidative stress compared with sedentary rats eating a regular diet; exercise‐trained rats eating a high‐fat diet had equivalent body weight, less body fat, and the same level of gingival oxidative stress as control rats 28 . It has been shown that individuals who walk for ≥30 minutes ≥5 days/week had lower circulating interleukin‐6 (IL‐6), tumor necrosis factor‐alpha (TNF‐α), and C‐reactive protein levels compared with individuals who engaged in less walking activity 29 . Although adipose tissue produces proinflammatory cytokines, such as TNF‐α, it was suggested that IL‐6, which is produced and released by contracting skeletal muscle fibers as a myokine, may be involved in mediating the anti‐inflammatory effect of exercise 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In an animal model, sedentary rats eating a high‐fat diet had greater body weight, more body fat, and gingival oxidative stress compared with sedentary rats eating a regular diet; exercise‐trained rats eating a high‐fat diet had equivalent body weight, less body fat, and the same level of gingival oxidative stress as control rats 28 . It has been shown that individuals who walk for ≥30 minutes ≥5 days/week had lower circulating interleukin‐6 (IL‐6), tumor necrosis factor‐alpha (TNF‐α), and C‐reactive protein levels compared with individuals who engaged in less walking activity 29 . Although adipose tissue produces proinflammatory cytokines, such as TNF‐α, it was suggested that IL‐6, which is produced and released by contracting skeletal muscle fibers as a myokine, may be involved in mediating the anti‐inflammatory effect of exercise 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other studies that have looked at IL-6 levels (27, 50), since the data was not normally distributed, values for IL-6 were log transformed [ln(IL-6 + 2)] in order to make the IL-6 variable better meet the assumptions of linear regression. Bivariate associations between IL-6 and the five health behavior variables (smoking, problem drinking, physical activity, BMI, and sleep), clinical covariates (cancer site and stage and comorbidities), and demographic variables (age, sex, race marital status, education, income) were assessed using Student t-tests and analysis of variance.…”
Section: Methodsmentioning
confidence: 99%
“…Regular mild exercise, such as walking has beneficial effects on IL-6 regulation (27), and on morbidity and mortality in cancer patients (28). While the acute response to exercise may actually increase IL-6 levels, perhaps due to stress to the muscles, the long term effects of exercise is lower IL-6 levels perhaps due to increased muscle mass and decreased adipose tissue, which secretes IL-6 (2931).…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses indicate that routine walking and other types of moderate aerobic exercise can improve glycemic control as indicated by decreased HbA1c [5, 6] and lower systolic blood pressure, triglycerides, and waist circumference [7]. Routine walking is also independently associated with lower levels of circulating proinflammatory markers [8], significant reduction of cardiovascular events [9], and lower cardiovascular mortality and all-cause mortality in adults with diabetes [10, 11]. …”
Section: Introductionmentioning
confidence: 99%